Bodenerosion und Bodenfeuchtebilanz in Zentralanatolien - Ein Beispiel für bewirtschaftete winterkalte Trockensteppen - Späth, Hans-Joachim (ERDKUNDE, 1975)
Modern summer fallowing - the purpose of which has been to increase soil moisture content - and overgrazing of agricultural and pastural dryland has caused heavy soil loss by water and wind in Central Anatolia. It was found that the seasonal variation in soil moisture content is a key factor in this process. Experiments of soil water conservation on fallowed soil show that early tillage can effectively disrupt capillary flow during the first stage of evaporation and that it creates an erosion resistant soil mulch. Conventional multiple fallow tillage, however, brings very little gain in moisture content and stimulates soil erosion. Thus the incompatible purpose and function suggest a re-evaluation of summer fallow. Windbarriers also are found to be effective for water conservation to such a degree that summer fallow could even be discontinued. This would be the best means of soil erosion control of all.